New insights of Enterobius vermicularis infection among preschool children in an urban area in Malaysia - Anuar, T.S.; Jalilah, L.; Norhayati, M.; Azlin, M.Y.; Fatmah, M.S.; Al-Mekhlafi, H.M. (De Gruyter Open, 2016)
Enterobiasis is a common intestinal parasitic infection caused by the nematode, Enterobius vermicularis. To assess the prevalence and to identify the underlying risk factors associated with enterobiasis among preschool children aged 1 - 6 years in Malaysia, 136 children from four nurseries and four kindergartens residing in the urban area were examined for Enterobius vermicularis. The cellotape anal swab technique was used for the detection of pinworm eggs. The parents/guardians of the investigated children were asked to complete the questionnaire so as to ascertain the potential risk factors for enterobiasis. The overall egg positive rate for Enterobius vermicularis infection was 12.5 %. The prevalence of this infection showed an age-dependency relationship, with higher rates observed among older children, aged 5 - 6 years. Multivariate analysis confirmed that finger sucking and belonging to a large family were significant risk factors of enterobiasis in the population studied. Recent pre-medication with anthelminthics was also found to have a significant impact on decreasing the egg positive rate for pinworm. The establishment of such data will be beneficial for the public health authorities in the planning and implementation of specific prevention in order to better control the infection.